2022
DOI: 10.1001/jamaoto.2021.3080
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of a Genomic Classifier in Indeterminate Thyroid Nodules Based on Nodule Size

Abstract: IMPORTANCE Genomic classifiers were developed to better guide clinicians in the treatment of indeterminate thyroid nodules (ITNs). To our knowledge, whether there is variation in the diagnostic accuracy of these tests depending on ITN size has not been previously studied. OBJECTIVETo analyze the diagnostic performance of a genomic classifier in relation to ITN size. DESIGN, SETTING, AND PARTICIPANTSA case series study with medical records review was conducted including all patients with a cytologic diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The data from the validation studies of the different molecular tests are showing that most of the ITNs after surgical resection are either benign, NIFTP or well-differentiated thyroid cancer with excellent prognoses [ 66 ]. There is a risk of having aggressive cancer in ITNs which is usually associated with the presence of aggressive mutations like BRAF-like mutations or high-risk mutations (e.g., TERT or TP53 ) [ 67 ]. Interestingly, a study by Turkodgan et al showed that in surgically resected ITNs, Bethesda III nodules are more likely to be aggressive than Bethesda IV nodules and molecular testing is strongly correlated with a higher risk of malignancy and aggressive features in these nodules [ 68 ].…”
Section: Clinical Utility and Our Group’s Experiencementioning
confidence: 99%
“…The data from the validation studies of the different molecular tests are showing that most of the ITNs after surgical resection are either benign, NIFTP or well-differentiated thyroid cancer with excellent prognoses [ 66 ]. There is a risk of having aggressive cancer in ITNs which is usually associated with the presence of aggressive mutations like BRAF-like mutations or high-risk mutations (e.g., TERT or TP53 ) [ 67 ]. Interestingly, a study by Turkodgan et al showed that in surgically resected ITNs, Bethesda III nodules are more likely to be aggressive than Bethesda IV nodules and molecular testing is strongly correlated with a higher risk of malignancy and aggressive features in these nodules [ 68 ].…”
Section: Clinical Utility and Our Group’s Experiencementioning
confidence: 99%
“…Although both false negative results occurred in nodules classified as Bethesda IV, the false negative rate for Bethesda IV lesions was only 5.7% and not significantly different from the other categories (P = . 19).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the missed malignancies in the current study were large suggesting that sampling error cannot account for the false negative results. Interestingly, Dublin and colleagues 19 recently published a review showing that the negative predictive value of ThyroSeq was actually higher in nodules over 4 cm (89%) compared with those less than 2 cm (79%). However, the overall rate of malignancy in their cohort of large nodules was substantially smaller than ours at less than 40% compared with our 64% which might account for the difference in negative predictive value between the 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that it is closely related to age and gender and other factors ( 21 ). The incidence of TN(s) in women is significantly higher than that in men ( 22 – 24 ), but the specific mechanism is not completely clear. It may be associated with overweight or obesity, hypertension, hyperglycemia, metabolic syndrome, sleep quality, etc.…”
Section: Introductionmentioning
confidence: 97%